Performance of The Front Office in Providing Services to Tourists Staying at The Kamarkoe Hotel - Selamet, I Wayan Agus; Satya Wira, Sang Nyoman Bagus; Sawokupu, Marselinus (Akademi Komunitas MAPINDO, 2023)
A hotel is a business that uses a specially provided building, where everyone can stay, eat, receive services anduse other facilities for a fee. The front office as a representative of the hotel and guest service management, isrequired to be able to handle and solve guest problems and complaints regarding service, facilities andemployee behavior professionally and efficiently in order to provide full satisfaction to guests. In this finalassignment the author explains the performance of the front office in providing services to tourists staying atthe Kamarkoe Hotel. This research method uses descriptive qualitative data with data collection techniques,namely observation, interviews, literature study and documentation. The purpose of this research is todetermine the performance of the front office in providing services to tourists staying at the Kamarkoe Hotel.The results of research on the performance of front office services at the Kamarkoe Hotel have maximallyimplemented the services provided by the front office staff.Keywords: E-marketing Model, New Normal